2021
DOI: 10.3847/1538-4357/abee75
|View full text |Cite|
|
Sign up to set email alerts
|

Implications of the Environments of Radio-detected Active Galactic Nuclei in a Complex Protostructure at z ∼ 3.3

Abstract: Radio active galactic nuclei (RAGNs) are mainly found in dense structures (i.e., clusters/groups) at redshifts of z < 2 and are commonly used to detect protoclusters at higher redshift. Here, we attempt to study the host and environmental properties of two relatively faint (L 1.4 GHz ∼ 1025 W Hz−1) RAGNs in a known protocluster at z = 3.3 in the PCl J0227-0421 field, detected using the latest radio observation obtained as part of the Observations of Redshift Evolution in Large-Scale Enviro… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

5
4

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 125 publications
2
6
0
Order By: Relevance
“…This result is consistent with the idea that Hot DOGs may not be the central galaxies of the overdensities traced by themselves (Assef et al 2015). It is worth noting that Shen et al (2021) also found similar results in the protostructure at z = 3.3 traced by radio-detected AGNs. They proposed a scenario where merging might already have happened in this case and lowered the local density of their surrounding region.…”
Section: Local Overdensity Of Drgssupporting
confidence: 89%
“…This result is consistent with the idea that Hot DOGs may not be the central galaxies of the overdensities traced by themselves (Assef et al 2015). It is worth noting that Shen et al (2021) also found similar results in the protostructure at z = 3.3 traced by radio-detected AGNs. They proposed a scenario where merging might already have happened in this case and lowered the local density of their surrounding region.…”
Section: Local Overdensity Of Drgssupporting
confidence: 89%
“…Navarro et al 1995;Borgani et al 2001), as well as the intergalactic medium (IGM; Borgani & Viel 2009), helping to narrow down the possible mechanisms that can lie behind the non-gravitational heat injection. Recently, a radio AGN has been found in a proto-cluster at redshift z = 3.3 (Shen et al 2021), which adds to the growing consensus that black hole feedback already plays a significant role in the early stages of the evolution of the ICM.…”
Section: Introductionmentioning
confidence: 84%
“…We complement DC 881725 with nine additional galaxies at z ∼ 4. et al 2009 ) surv e y (C3VO; Lemaux et al 2020 ;Shen et al 2021 ).…”
Section: [O II ] Measurements From Narrow-band Imagingmentioning
confidence: 99%